A composiç\~ao da estrutura produtiva agrícola da agricultura familiar brasileira no ano de 2017: O caminho da comoditizaç\~ao? - Murilo José de Souza Pires (Instituto de Pesquisa Econômica Aplicada (IPEA), 2024)
– The objective of this investigation was to analyze the characteristics of the agricultural structures of Brazilian family farming, in its multi-scale forms, as well as its aspects of location and specialization. Therefore, it was observed that the production structure of family farming in Brazil has shown similarities with the production structure of national agriculture. Evidence of productive specialization in products related to agricultural commodities indicates that family farming is also turning to these products. However, there is a reduction in the production of crops related to the domestic market, with the exception of cassava. This change could affect food and nutritional security policy in the future, as well as negatively impact food prices in the country.
Keywords: R11; 330; family farming; agricultural commodities; food security